2014
DOI: 10.1016/j.nlm.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and extinction: A convergence of theory with fear and reward circuitry

Abstract: Research on dopamine lies at the intersection of sophisticated theoretical and neurobiological approaches to learning and memory. Dopamine has been shown to be critical for many processes that drive learning and memory, including motivation, prediction error, incentive salience, memory consolidation, and response output. Theories of dopamine’s function in these processes have, for the most part, been developed from behavioral approaches that examine learning mechanisms in reward-related tasks. A parallel and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
144
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(149 citation statements)
references
References 134 publications
(177 reference statements)
3
144
1
1
Order By: Relevance
“…There are many possibilities for this, including consolidation of the prediction error that occurred in extinction (Abraham et al, 2014), a D1-mediated prolonged window of inhibitory memory activity (Wagner, 1981), or counterconditioning of aversive fear memory by the rewarding properties of SKF81297 (Holmes and Westbrook, 2014). Our findings that SKF81297 induced a CPP when it was used as the US suggest that counterconditioning is a possibility for the enhanced fear extinction effects, and previous studies have shown that fear learning is subject to opponent interactions between appetitive and aversive processes (Nasser and McNally, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There are many possibilities for this, including consolidation of the prediction error that occurred in extinction (Abraham et al, 2014), a D1-mediated prolonged window of inhibitory memory activity (Wagner, 1981), or counterconditioning of aversive fear memory by the rewarding properties of SKF81297 (Holmes and Westbrook, 2014). Our findings that SKF81297 induced a CPP when it was used as the US suggest that counterconditioning is a possibility for the enhanced fear extinction effects, and previous studies have shown that fear learning is subject to opponent interactions between appetitive and aversive processes (Nasser and McNally, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that the long-term consolidation of extinction memories involves dopaminergic signalling (Abraham et al, 2014(Abraham et al, , 2012Haaker et al, 2013a;Holtzman-Assif et al, 2010;Mueller et al, 2010;Singewald et al, 2015). We have found in mice that systemic administration of the dopamine precursor L-DOPA immediately after extinction learning (i.e., during memory consolidation) prevents the ROF that normally occurs upon CS re-confrontation in a spatial context that is different from the extinction context (renewal), after a mere passage of time (spontaneous recovery), or after prior re-confrontation with the US (reinstatement) (Haaker et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…The timehonored D1-family antagonist SCH23390 (SCH) does not discriminate between D1 and D5 receptors, and drugs acting on enzymes downstream of them have to be used to see if a given effect blocked by this drug is due to one or the other (29). It has been recently found to control the enhancing effect of novelty on spatial alimentary conditioning and its accompanying LTP, which was also attributed to a tagging-and-capture mechanism (35).D1 and D5 dopamine receptors are expressed in the CA1 region of the hippocampus and play a role in hippocampal neuroplasticity and memory, but they can have different roles in different tasks and situations (28,32,33,36). Also, both PKA and PKC participate in the modulation of hippocampal synaptic plasticity and memory consolidation (6).…”
mentioning
confidence: 99%
“…Discrimination between the two types of D1-family receptors is possible by the simultaneous administration of drugs acting on PKA and PKC (29). Both D1-family receptor types are expressed in brain regions important for learning and memory, such as the hippocampus and amygdala (30, 31), and affect learning and memory (29,(32)(33)(34). The timehonored D1-family antagonist SCH23390 (SCH) does not discriminate between D1 and D5 receptors, and drugs acting on enzymes downstream of them have to be used to see if a given effect blocked by this drug is due to one or the other (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation